Safety and immunological effectiveness of the domestic combined trivaccine for the prevention of measles, rubella and mumps Vaktrivir® in children 12 months and 6 years of age (results of a simple blind multicenter comparative randomized clinical trial) - I. V. Feldblium; V. V. Romanenko; K. A. Subbotina; M. G. Menshikova; I. A. Okuneva; A. Y. Musikhina; T. E. Snitkovskaya; N. I. Marcovich; A. E. Ershov; D. M. Trofimov (Эпидемиология и вакцинопрофилактика)
Relevanc. Measles, mumps and rubella, despite many years of vaccination, retain their epidemiological and social significance at the present time. The aim of the work is to study the safety and immunogenicity. Of the vaccine for the prevention of measles, rubella and mumps Vactrivir® in children's immunization. Materials and methods. The safety and immunogenicity of the vaccine was studied in a simple multicenter blind comparative randomized clinical trial involving children aged 12 months and 6 years. Results. The Vactrivir® vaccine is characterized by low reactogenicity, a high safety and immunogenicity profile and is comparable in terms of indicators to the foreign Priorix® vaccine, which has been used in the Russian Federation for specific prevention of measles, rubella and mumps since 2018.